Ecological and agronomic importance of the plant genus Lotus. Its application in grassland sustainability and the amelioration of constrained and contaminated soils - Escaray, Francisco José (2012)
The genus Lotus comprises around 100 annual and perennial species with worldwide distribution. The relevance of Lotus japonicus as a model plant has been recently demonstrated in numerous studies. In addition, some of the Lotus species show a great potential for adaptation to a number of abiotic stresses. Therefore, they are relevant components of grassland ecosystems in environmentally constrained areas of several South American countries and Australia, where they are used for livestock production. Also, the fact that the roots of these species form rhizobial and mycorrhizal associations makes the annual L. japonicus a suitable model plantfor legumes, particularly in studies directed to recognize the mechanisms intervening in the tolerance to abiotic factors in the field, where these interactions occur. These properties justify the increased utilization of some Lotus species as a strategy for dunes revegetation and reclamation of heavy metal-contaminated or burned soils in Europe.